Jaranan Culture as A Means of Role-Playing for Children Aged 4-5 Years - Oktaviana, Revi; Kusumastuti, Narendradewi; Tanto, Octavian Dwi (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to describe a finding made by researchers regarding jaranan arts and culture as a means of playing the role of children aged 4-5 years in the Sambong hamlet area, Karangjati sub-district, Ngawi district. This research is qualitative research using an ethnographic approach. The results of this study indicate that role-playing can be carried out through jaranan cultural arts activities in the form of playing the role of being a handler, caplokan or dragon snake, lumping horse, wild boar or wild boar, becoming a person possessed, and playing the role of being a pin. The purpose of this study was to determine the form, process, and supporting and inhibiting factors of jaranan cultural art as a means of playing the role of children aged 4-5 years.